6. Q6f
Save videos to My Cheatsheet for later, for easy studying.
Video Solution
Q1
Q2
Q3
L1
L2
L3
Similar Question 1
<p>Use the distributive property to find the binomial product.</p><p><code class='latex inline'> \displaystyle (x - 1)(x -4) </code></p>
Similar Question 2
<p>Expand and simplify.</p><p><code class='latex inline'>(a+5)(a+6)</code></p>
Similar Question 3
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(x+3)(x-7)</code></p>
Similar Questions
Learning Path
L1 Quick Intro to Factoring Trinomial with Leading a
L2 Introduction to Factoring ax^2+bx+c
L3 Factoring ax^2+bx+c, ex1
Now You Try
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(y + 2)(y + 4)</code></p>
<p> Expand the following. Before expanding, simplify the signs of the terms inside each brackets if possible.</p><p><code class='latex inline'> (c - a)(2c - 3a) </code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>\displaystyle (z - 7x)(z- 8x) </code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>\displaystyle (y - 9)(y + 3)</code></p>
<p>Find each binomial product.</p><p><code class='latex inline'>\displaystyle (6q + 5r)(7q - 12r)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>\displaystyle (q -4)(q -2) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(x+3)(x+4)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>\displaystyle (p - 9)(p - 3) </code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(x+7)(x+4)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(x+2)(x+5)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>\displaystyle (x - 2)(x - 4)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(h-1)(h-4)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>\displaystyle (b - 3c)(b - 11c) </code></p>
<p>Expand the following.</p><p><strong>a)</strong> <code class='latex inline'> \displaystyle (x + 3)(x + 4) </code></p><p><strong>b)</strong> <code class='latex inline'> \displaystyle (x + 3)(x - 4) </code></p><p><strong>c)</strong> <code class='latex inline'> \displaystyle (x - 2)(x - 2) </code></p><p><strong>d)</strong> <code class='latex inline'> \displaystyle (x + 2 (x- 3) </code></p><p><strong>e)</strong> <code class='latex inline'> \displaystyle (x - 2)(x - 3) </code></p><p><strong>f)</strong> <code class='latex inline'> \displaystyle (x + 2)(x - 2) </code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(r + 4)(r +2)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(r-8)(r+3)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(z+8)(z+8)</code></p>
<p>Multiply.</p><p><code class='latex inline'>\displaystyle (3 y-2)(y-4) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(b+7)(b+3)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(x-5)(x-6)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(x-3)(x-5)</code></p>
<p>Use the distributive property to find the binomial product.</p><p><code class='latex inline'> \displaystyle (x + 5)(x + 8) </code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(y+6)(y+1)</code></p>
<p> Expand the following. Before expanding, simplify the signs of the terms inside each brackets if possible.</p><p><code class='latex inline'> (a + b)(a - b) </code></p>
<p>Find each binomial product.</p><p><code class='latex inline'>\displaystyle (5m + 6)(5m -6)</code></p>
<p>Use the distributive property to find the binomial product.</p><p><code class='latex inline'> \displaystyle (x + 3y)(x -6y) </code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(w+ 7)(w + 8)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(d + 3)(d + 11)</code></p>
<p> Expand the following. Before expanding, simplify the signs of the terms inside each brackets if possible.</p><p> <code class='latex inline'>\displaystyle (a + b)(a - b) </code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(e-5)(e+6)</code></p>
<p>Expand and simplify each expression.</p><p><code class='latex inline'>\displaystyle (n + 3)(n - 3) </code></p>
<p>Find each binomial product.</p><p><code class='latex inline'>\displaystyle (7w -2)(2w + 1)</code></p>
<p>Use the distributive property to find each binomial product.</p><p> <code class='latex inline'>(x +3)(x + 5)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>\displaystyle (4x -7)(3x + 2) </code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>\displaystyle (c - 2)(c + 4)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>\displaystyle (y -3)(y - 4)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(x+2y)(x-5y)</code></p>
<p>A parabola has equation <code class='latex inline'>y = (x + 3)(x - 1)</code> expand and simplify the equation.</p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(q+5)(q+10)</code></p>
<p>Apply the distributive property to simplify the following. </p><p><code class='latex inline'>(2x+y)(x+y)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(m-2)(m-7)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(w+2)(w+8)</code></p>
<p>Find each binomial product.</p><p><code class='latex inline'>\displaystyle (6c -1)(3c + 5)</code></p>
<p>Use the distributive property to find each binomial product.</p><p> <code class='latex inline'>\displaystyle (y + 3)(y -4)</code></p>
<p>Find each product.</p><p><code class='latex inline'>\displaystyle (p-9)(p+1) </code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>\displaystyle (w -4)(w + 2)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(d+3)(d+2)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(x+1)(x+3)</code></p>
<p> Expand the following. Before expanding, simplify the signs of the terms inside each brackets if possible.</p><p><code class='latex inline'> (c - 2)( - 2c - 2) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(m-4)(m+5)</code></p>
<p>Model each binomial product using algebra tiles, virtual algebra tiles, or a diagram.</p><p><code class='latex inline'>(3x+1)(2x+3)</code></p>
<p>Find the product.</p><p><code class='latex inline'>\displaystyle (a+5)(a-6) </code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(k-6)(k-6)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(p + 9)(p + 9)</code></p>
<p>Apply the distributive property to simplify the following. </p><p><code class='latex inline'>(y+2)(y+1)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>-(k-3)(k+5)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(x+3)(x-7)</code></p>
<p>Find the product.</p><p><code class='latex inline'>\displaystyle (x-2)(x+4) </code></p>
<p>Find each binomial product.</p><p><code class='latex inline'>\displaystyle (9y-2)(2y + 2)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>\displaystyle (j - 7)(j -1) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(h-4)(h-8)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>\displaystyle (k -3)(k - 5)</code></p>
<p>Find each binomial product.</p><p><code class='latex inline'>\displaystyle (y - 3)(5y - 7)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(d+5)(d-2)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(x-3)(x-4)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(h+9)(h-5)</code></p>
<p>Use the distributive property to find each binomial product.</p><p> <code class='latex inline'>\displaystyle (x + 3)(x -5)</code></p>
<p> Expand the following. Before expanding, simplify the signs of the terms inside each brackets if possible.</p><p> <code class='latex inline'>\displaystyle (c - a)(2c - 3a) </code></p>
<p>Find each product.</p><p><code class='latex inline'>\displaystyle (y+2)(y-1) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(y-5)(y+3)</code></p>
<p>Use the distributive property to find the binomial product.</p><p><code class='latex inline'> \displaystyle (x - 1)(x -4) </code></p>
<p>Model each binomial product using algebra tiles, virtual algebra tiles, or a diagram.</p><p><code class='latex inline'>(x+2)(x+1)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>\displaystyle (m + 7)(m - 1)</code></p>
<p>Expand each pair of binomials, Compare the answers.</p><p><code class='latex inline'>(x+4)(x-6)</code> and <code class='latex inline'>(x+4y)(x-6y)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(a+5)(a+6)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(x+5)(x-4)</code></p>
<p>Find each binomial product.</p><p><code class='latex inline'>\displaystyle (7d + 5c)(8d - 6c)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>\displaystyle (y + 5)(y+ 9) </code></p>
<p>Find the product.</p><p><code class='latex inline'>\displaystyle (2 y-3)(3 y+4) </code></p>
<p>Use the distributive property to find the binomial product.</p><p><code class='latex inline'> \displaystyle (5a -6b)(2a + 9b) </code></p>
<p>Model each binomial product using algebra tiles, virtual algebra tiles, or a diagram.</p><p><code class='latex inline'>(x+3)(x+4)</code></p>
<p>Use the distributive property to find each binomial product.</p><p> <code class='latex inline'>(x + 3)(x + 4)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(n-4)(n+6)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(4a-3b)(2a+5b)</code></p>
<p>Model each binomial product using algebra tiles, virtual algebra tiles, or a diagram.</p><p><code class='latex inline'>(3x+2)(2x+1)</code></p>
<p>Use the distributive property to find each binomial product.</p><p> <code class='latex inline'>\displaystyle (x + 7y)(x - 8y)</code></p>
<p>Use the distributive property to find each binomial product.</p><p> <code class='latex inline'>\displaystyle (a + 6b)(a -10b)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>(z+3)(z-6)</code></p>
<p>Find each product.</p><p><code class='latex inline'>\displaystyle (b-7)(b-3) </code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(n + 7)(n + 1)</code></p>
<p>Find each binomial product.</p><p> <code class='latex inline'>\displaystyle (2x + 3)(x + 4)</code></p>
<p>Use the distributive property to find each binomial product.</p><p><code class='latex inline'>(a-6)(a-8)</code></p>
How did you do?
Found an error or missing video? We'll update it within the hour! ðŸ‘‰
Save videos to My Cheatsheet for later, for easy studying.